2006
DOI: 10.1002/bio.925
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive inhibition chemiluminescence method for the determination of trace tannic acid using the reaction of luminol–hydrogen peroxide catalysed by tetrasulphonated manganese phthalocyanine

Abstract: A novel CL method for the determination of tannic acid (TA) was established based on TA inhibition of the chemiluminescence (CL) emission of the luminol-hydrogen peroxide CL system catalysed by tetrasulphonated manganese phthalocyanine (MnTSPc) under alkaline conditions. The peak height is proportional to the natural logarithm of concentration of TA in the range 1.0 x 10(-7)-3.0 x 10(-10) mol/L with a detection limit of 5.6 x 10(-11) mol/L and the relative standard deviation was 2.5% for the determination of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…At present, determination of tannic acid by CL methods is mainly based on CL emission from the luminol reaction, such as luminol-K 3 Fe(CN) 6 , [8] luminal-KIO 4 , [9] luminol-KIO 4 -Mn 2+ [10] and luminal-H 2 O 2 -Cu 2+ . [11] Yang et al [12] reported that tannic acid can inhibit CL from luminal-hydrogen peroxide catalyzed by tetrasulfonated manganese phthalocyanine, which was applicable for the detection of trace tannic acid in Chinese gall and industrial wastewater. In this work, the effect of tannic acid on kinetic curves of the CL systems of KIO 4 -H 2 O 2 and KIO 4 -H 2 O 2 -Tween40 was systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…At present, determination of tannic acid by CL methods is mainly based on CL emission from the luminol reaction, such as luminol-K 3 Fe(CN) 6 , [8] luminal-KIO 4 , [9] luminol-KIO 4 -Mn 2+ [10] and luminal-H 2 O 2 -Cu 2+ . [11] Yang et al [12] reported that tannic acid can inhibit CL from luminal-hydrogen peroxide catalyzed by tetrasulfonated manganese phthalocyanine, which was applicable for the detection of trace tannic acid in Chinese gall and industrial wastewater. In this work, the effect of tannic acid on kinetic curves of the CL systems of KIO 4 -H 2 O 2 and KIO 4 -H 2 O 2 -Tween40 was systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most efficient CL systems is a luminolhydrogen peroxide mixture. [6][7][8] Oxidation of luminol with hydrogen peroxide produces 3-aminophthalate ions in an excited state (3-aminophthalate*), which emits light upon relaxation to the ground state. This reaction proceeds effectively under alkaline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the main difficulty in the determination of FZD is its instability due to sensitivity to light [12], there is now an urgent need for a rapid, simple, and sensitive determination method for FZD at low concentrations in animal feed, in order to satisfy needs on feed control. Chemiluminescence (CL) analysis has received much attention for the analysis of organic species in a variety of fields for its high sensitivity, wide dynamic range and inexpensive instrumentation [13][14]. However, the CL signal of normal CL systems containing FZD was relatively weak.…”
Section: Introductionmentioning
confidence: 99%